Plasma interleukin-10 levels and adverse outcomes in acute coronary syndrome - Cavusoglu, Erdal; Marmur, Jonathan D; Hojjati, Mohammad R; Chopra, Vineet; Butala, Mitul; Subnani, Rakesh; Huda, Mohammad S; Yanamadala, Sunitha; Ruwende, Cyril; Eng, Calvin; Pinsky, David J (The American journal of medicine, 2011)
PURPOSE OR BACKGROUND: Interleukin (IL)-10 is an immunoregulatory cytokine that is produced by a variety of cell types, such as macrophages and activated monocytes. IL-10 possesses numerous anti-inflammatory, anti-thrombotic and anti-atherosclerotic properties. Furthermore, patients with acute coronary syndrome have been demonstrated to have reduced levels of IL-10 compared to their stable counterparts. For these reasons, it has been proposed that IL-10 plays a protective role in both atherogenesis and plaque vulnerability. However, 2 short-term studies on the prognostic utility of IL-10 in patients with acute coronary syndrome have provided conflicting results, with one study showing that reduced levels of IL-10 were predictors of adverse outcomes and another showing that elevated levels predicted poor outcomes. The objective of the present study was to investigate the long-term prognostic significance of baseline IL-10 levels in patients with acute coronary syndrome. Baseline plasma IL-10 levels were measured in 193 well-characterized male patients with acute coronary syndrome who were referred for coronary angiography and followed prospectively for 5 years for the development of major adverse cardiovascular events. After controlling for a variety of baseline variables (including established biomarkers such as high-sensitivity C-reactive protein and N-terminal-pro-B-type natriuretic peptide), plasma IL-10 levels (whether analyzed as a continuous variable or as a categorical variable using receiver operating characteristic-derived cut point) were a strong and independent predictor of the composite outcome of death or non-fatal myocardial infarction when using a Cox proportional hazards model. These data demonstrate that, despite biologic plausibility for IL-10 as being a cardioprotective cytokine, elevated baseline plasma levels of IL-10 are a strong and independent predictor of long-term adverse cardiovascular outcomes in patients with acute coronary syndrome.